Incorporate Indigenous perspectives for impactful research and effective management. Issue 11 (November 2018) - Ban, Natalie; Frid, Alejandro; Reid, Mike; Edgar, Barry; Shaw, Danielle; Siwallace, Peter
Indigenous knowledge and ecological science have complementary differences that can be fruitfully combined to better understand the past and predict the future of social-ecological systems. Cooperation among scientific and Indigenous perspectives can improve conservation and resource management policies.